The Influence Of Human Resources Development And Training On Employee Performance In The Water Resources Management Service Of Lampung Province - Rachman, Liza Oktaviani; Sodirin, Sodirin (Universitas Dehasen Bengkulu, 2025)
The success of an organization or agency depends on the quality of the human resources working in it. Rapid changes in the business world and globalization require the organization's ability to adapt and analyze these changing phenomena and their impact on the organization and prepare strategies to deal with these conditions. Based on these facts, the role of human resource management in organizations is not just administrative but must be more focused on solutions to be able to develop the potential of human resources to be more creative and innovative. To be able to carry out their duties well, employee development is directed at improving the quality of human resources so that they have attitudes and behavior that are based on devotion, honesty, responsibility, discipline and authority so that they can provide services in accordance with the demands of community development. Efforts to realize this require coaching, improving the government apparatus including increasing knowledge, abilities, increasing dedication as well as efforts to create a government apparatus that is clean and authoritative, creative, efficient and successful in order to ensure civil servant discipline is required. The aim of this research is to determine: 1. The influence of human resource development on employee performance 2. The influence of training on employee performance 3. The influence of human resource development and training together on employee performance at the Lampung Province Water Resources Management Service (DPSDA). This research uses a quantitative descriptive research method, namely a research method that uses data in the form of numbers to analyze the facts found which aims to determine the relationship between variables in a population. The analysis used is simple and multiple regression. This research used 54 respondents. Based on the results of data analysis, the hypothesis answer was found as follows; There is an influence of HR Development (X1) on Employee Performance (Y) at the Lampung Province Water Resources Management Service, with an influence level (R-square) of 50.4%. There is an influence of training on employee performance at the Lampung Province Water Resources Management Service with an influence level of 78.9%. There is an influence of HR Development and Training together on the Performance of the Lampung Province Water Resources Management Service Employees, with an influence level of 81.3%